The role of sex education in withdrawal use: Prevalence and correlates among a nationally representative sample of adolescents and young adults - John L. Ferrand; Arthur H. Owora; Alexandra T. Hughes-Wegner; Eric R. Walsh-Buhi (PLoS ONE, 2026)
Objectives Instances of withdrawal, the practice of removing a penis from a vagina before ejaculation to prevent pregnancy, have increased in some US populations over the past two decades. There is a paucity of research, however, on the prevalence and correlates of withdrawal among adolescents and young adults (AYAs). This study sought to determine the prevalence and correlates of withdrawal use in a representative sample of AYAs in the US, highlighting the association between receipt of informal sexuality education and withdrawal use. Study design We analyzed cross-sectional National Survey of Family Growth data from AYAs surveyed between 2011 and 2019 (15–24 years; N = 14,262). Prevalence of withdrawal was determined using different sexual activity time-points (at first sex and ever) and reference periods (past 3 and 12 months). Logistic regression models were used to identify correlates of withdrawal alone and combined with at least one other method. Results Across all waves and reference periods, the prevalence of withdrawal was higher among AYAs who combined it with at least one other method (ever [overall]=15.15, SE = 0.58) compared with those who used it as the only method (ever [overall]=8.32, SE = 0.38). Compared to the 2011–2013 wave, those in the 2015–2017 wave had greater odds of reporting using only withdrawal in the past 3 months (AOR: 1.50; 95% CI: 1.02, 2.21). The same trend was seen in those who used withdrawal with another method at last sex in the past 3 and 12 months. Withdrawal alone or combined with another method varied by receipt of informal sexuality education topics (e.g., methods of birth control vs STIs). Conclusion Variations in use of withdrawal based on type of informal sexuality education received suggests that different motivations might inform interventions in promoting effective reproductive health practices.